2012
DOI: 10.1002/chem.201103129
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Homo‐ and Heteromolecular Hydrogen Bonds as a Guide for Adduct Formation

Abstract: An investigation into the predictability of molecular adduct formation is presented by using the approach of hydrogen bond propensity. Along with the predictions, crystallisation reactions (1a-1j) were carried out between the anti-malarial drug pyrimethamine (1) and the acids oxalic (a), malonic (b), acetylenedicarboxylic (c), adipic (d), pimelic (e), suberic (f), azelaic acids (g), as well as hexachlorobenzene (h), 1,4-diiodobenzene (i), and 1,4-diiodotetrafluorobenzene (j); seven (1a to 1g) of these successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
74
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 63 publications
2
74
0
1
Order By: Relevance
“…In particular, though they deposited the crystallographic data for this phase at the CSD (refcode XEGJEA), no description of the structure, morphology, thermodynamic properties or solubility profile were presented in their manuscript. The present account in part, serves to elaborate on the physicochemical properties of PyrMeOH, being distinctly unrelated to the study by Delori et al (7). We found that recrystallization may not only risk the alteration of the toxicity of anhydrous pyrimethamine, but also its manufacturability.…”
Section: Introductionmentioning
confidence: 50%
See 4 more Smart Citations
“…In particular, though they deposited the crystallographic data for this phase at the CSD (refcode XEGJEA), no description of the structure, morphology, thermodynamic properties or solubility profile were presented in their manuscript. The present account in part, serves to elaborate on the physicochemical properties of PyrMeOH, being distinctly unrelated to the study by Delori et al (7). We found that recrystallization may not only risk the alteration of the toxicity of anhydrous pyrimethamine, but also its manufacturability.…”
Section: Introductionmentioning
confidence: 50%
“…The focus of the work done by Delori et al (7) was completely different to that which is presented herein. The work of Delori et al (7) focused on the formation of co-crystals and salts of pyrimethamine, with the formation of Pyr-MeOH as a mere by-product of their study, being allocated, in passing, only two sentences in their manuscript (7). In particular, though they deposited the crystallographic data for this phase at the CSD (refcode XEGJEA), no description of the structure, morphology, thermodynamic properties or solubility profile were presented in their manuscript.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations